The role of nonsteroidal anti‐inflammatory drugs intramuscular injection in the development and severity of deep soft tissue infection in mice. (15th December 2017) - Ture, Zeynep; Demiraslan, Hayati; Kontas, Olgun; Alp, Emine; Doganay, Mehmet
Abstract: The aim of this study was to determine the role of nonsteroidal anti‐inflammatory drugs (NSAID) injection on the severity of local infection and the effect on the progression of soft tissue infection (STI).The mouse model of STI with Group A streptococcus (GAS) was developed and treated with diclofenac sodium (DS) intramuscularly. Mice were divided into five groups: administered DS for 48 h before GAS (Group 1), GAS‐DS and maintained DS for 48 h (Group 2), DS for 48 h (Group 3), GAS on zero time (Group 4), and control (Group 5). In vitro, a high concentration (40 mg/L) of DS inhibited GAS growth, whereas a lower concentration (0.4 mg/L) was not effective. Sepsis was observed in animals with DS and GAS inoculation (group 1 and 2). Group 4 had statistically significant higher bacterial load than groups 1 and 2. All groups had a higher inflammation rate than the control group. The median of TNF‐alpha and mean IL‐6 in the groups 1, 2, and 4 was significantly higher than those in the control group. Even if the animals that were treated with DS injection prior to the GAS inoculation had similar inflammation score, similar cytokine levels and low bacterial load in the tissue, they had a rather high rate of sepsis. In conclusion, DS injection prior to bacterial inoculation might predispose to bacteremia and sepsis.